Plantas para cercos comercializadas en una ciudad costera de la Patagonia extra-Andina (Argentina): atributos de selección e implicancias para la conservación - Barrientos, Elizabeth (2025)
Background and aims: Building living fences at home is a common practice worldwide. However, little is known about the selection criteria and trade of ornamental species for this purpose. This study surveyed the richness of species sold for fences in nurseries in Comodoro Rivadavia, the attributes related to their differential importance, and their invasive potential. M&M: The species sold in the city’s 17 nurseries were listed and photographed. In addition, semi-structured interviews were conducted with the sellers, and ecological information was completed through a bibliographic review. The sales ranking was estimated, and the data were analyzed using qualitative and multivariate methods. Results: The nurseries offer a total richness of 47 species (3 minimum, 16 maximum), including five native species and two endemics (Atriplex lampa and Pappostipa humilis). The species with the highest ranking were Viburnum tinus, Buxus sempervirens, Phormium tenax, Cupressus x leylandii, and Populus alba. Species with aesthetic (64%) and acclimatization (16%) attributes have the highest sales rankings. Four species (Hedera helix, Lonicera japonica, Ligustrum sinense, and Cupressus sempervirens) are invasive in other parts of the world, although their behaviour in the study region is unknown. Conclusions: The supply of fence species is consistent with the Holarctic pattern of ornamental plant use. We propose to consider the preferred attributes for the promotion of native species with potential value in the construction of living fences.